Optimization Path and Effectiveness Evaluation of Differentiated Instruction Strategies in Education - Li, Jing (Journal of Cross-Disciplinary Sustainability Innovations, 2025)
Differentiated instruction plays a pivotal role in modern educational practice. By tailoring teaching methods and employing diverse pedagogical approaches, it effectively addresses individual student differences, fostering personalized development and enhancing comprehensive competencies. Through literature review, case studies, and empirical research, this study establishes a scientifically grounded optimization framework for differentiated instruction, encompassing differentiated objectives, content, methodologies, and assessments. During implementation, strategies such as flexible goal-setting, evidence-based method selection, optimized content organization, and multidimensional evaluation have proven effective in stimulating student engagement, improving autonomous learning capabilities, and elevating overall teaching efficacy. The application of differentiated instruction not only promotes holistic student development but also provides practical guidance for enhancing teachers’ instructional proficiency.